2014
DOI: 10.1007/s11524-014-9920-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Surveillance among Youth and Young Adults in New York City, 2009–2013

Abstract: Increases in prescription opioid misuse, injection drug use, and hepatitis C infections have been reported among youth and young adults in the USA, particularly in rural and suburban areas. To better understand these trends in New York City and to characterize demographics and risk factors among a population who, by virtue of their age, are more likely to be recently infected with hepatitis C, we analyzed routine hepatitis C surveillance data from 2009 to 2013 and investigated a sample of persons 30 and younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…As in prior studies (Armstrong, 2007; Broz and Ouellet, 2008; Broz et al, 2014; Garfein et al, 1998; Hahn et al, 2010; Neaigus et al, 2006; Ochoa et al, 2001; Prussing et al, 2014; Pugatch, 2006), our study showed that young PWID are likely to be non-Hispanic white (71%), even though our recruitment sites were located in urban, predominantly African American and Hispanic neighborhoods. A main finding of our study is that homelessness and residential transience are integral components of HCV and HIV risk, mediated through network size and syringe sharing.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As in prior studies (Armstrong, 2007; Broz and Ouellet, 2008; Broz et al, 2014; Garfein et al, 1998; Hahn et al, 2010; Neaigus et al, 2006; Ochoa et al, 2001; Prussing et al, 2014; Pugatch, 2006), our study showed that young PWID are likely to be non-Hispanic white (71%), even though our recruitment sites were located in urban, predominantly African American and Hispanic neighborhoods. A main finding of our study is that homelessness and residential transience are integral components of HCV and HIV risk, mediated through network size and syringe sharing.…”
Section: Discussionsupporting
confidence: 70%
“…Concurrent with these trends has been a demographic and geographic shift in the profile of young PWID across the United States (U.S.), who are increasingly from suburban communities and predominantly non-Hispanic (NH) white (Armstrong, 2007; Broz and Ouellet, 2008; Broz et al, 2014; Neaigus et al, 2006; Prussing et al, 2014). In the few recent U.S. studies that specifically focused on young PWID (≤ 30 years old), NH-whites were the dominant racial/ethnic group, and African Americans constituted only small fractions of the samples (Garfein et al, 2007; Hahn et al, 2010; Ochoa et al, 2001; Pugatch, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the growing body of scientific literature that demonstrates increasing concerns about substance misuse, injection-mediated risks, and a constellation of comorbidities within younger populations [1214, 16, 21, 28–33]. Our results provide additional insights into the complex mix of infectious diseases that face PWID and are a harbinger of healthcare utilization patterns to come among young adults in the throes of addiction.…”
Section: Discussionsupporting
confidence: 51%
“…Previous reports suggest that heroin, cocaine, and combinations thereof (known as ‘speedballs’) are overwhelmingly the most commonly injected drugs in NYC (New York City Department of Health and Mental Hygiene, 2010, 2013). Additionally, high rates of hepatitis C have been detected in individuals under 30 years old in NYC with the most common risk factor being heroin injection (Prussing, Bornschlegel, & Balter, 2015). …”
Section: Introductionmentioning
confidence: 99%